Imitation learning for autonomous driving: disagreement-regularization and behavior cloning with beta distribution - Petrazzini, Irving Giovani Bronzatti (2023)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2023.